Relationship between mobility, violence and major depression among female sex workers: a cross-sectional study in southern India. Issue 9 (9th September 2016) - Patel, Sangram Kishor; Ganju, Deepika; Prabhakar, Parimi; Adhikary, Rajatashuvra
Abstract : Background: The relationship between mobility, violence and mental health has largely been unexplored in developing countries. This study screens for signs of major depression, and assesses its association with mobility and violence among female sex workers (FSWs) in southern India. Methods: Data (N=2400) for this study were used from a cross-sectional Behavioral Tracking Survey (BTS-2014) conducted among FSWs from a southern state of India as part of the Avahan programme. Major depression of FSWs was assessed using the Patient Health Questionnaire-2 depression scale. Descriptive statistics, frequency, bivariate, interaction effect and multivariate logistic regression techniques were used for the analysis. Results: More than one-fourth of FSWs (29%) screened positive for major depression. The likelihood of screening positive for major depression was 6 times higher among FSWs who were both mobile for sex work outside their district of residence and had experienced any violence (combined association) during the past 1 year (62% vs 19%, adjusted OR 6.1, 95% CI 4.4 to 8.6) compared with those who reported neither. The individual association results show that FSWs who reported being mobile outside the district, and FSWs who were beaten or raped in the past 1 year, were 3 times more likely to screen positive for major depression. Conclusions: The findings indicate that violence and mobility are independently associated with major depression among FSWs. The combined association of mobility and violence poses a greater risk to the mental health of FSWs than their independent association. These results point to the need for creating an enabling environment for FSWs to enhance existing efforts to reduce the spread of HIV and mental health problems. The study highlights that HIV prevention efforts among FSWs in India require evidence-based research and integrated programme approaches to address mental health issues.